2016
DOI: 10.1186/s13071-016-1416-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population genetics of the warble flies Hypoderma bovis and H. sinense in Qinghai Province, China

Abstract: BackgroundHypoderma bovis and H. sinense (Diptera: Oestridae) mainly parasitise cattle and yaks. The two parasites are pathogenic and cause economic losses that result from reduced amounts of livestock products, including milk, meat, and skin. Genetic diversity and population genetic structure of H. bovis and H. sinense have not been evaluated, but could be used to inform appropriate strategies to control these parasites.MethodsWe cloned and sequenced part of the mitochondrial cytochrome c  oxidase subunit I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…H. bovis is frequently reported in countries from the northern hemisphere, and its pathogeny is of greater importance to farmers, considering the severity of lesions that this infection might induce if treatment is not instituted promptly (when first-stage larvae are in the peri-rachidian channel, in the absence of treatment, they might induce paralysis of the hind quarters) [13]. The results of the morphological identification doubled by PCR assays based on mitochondrial COI sequencing for the identification of H. bovis [28] performed during our study revealed the presence of H. bovis with two haplotypes: HB3 and HB8. Another study based on molecular characterisation, conducted by Otranto et al [29], revealed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…H. bovis is frequently reported in countries from the northern hemisphere, and its pathogeny is of greater importance to farmers, considering the severity of lesions that this infection might induce if treatment is not instituted promptly (when first-stage larvae are in the peri-rachidian channel, in the absence of treatment, they might induce paralysis of the hind quarters) [13]. The results of the morphological identification doubled by PCR assays based on mitochondrial COI sequencing for the identification of H. bovis [28] performed during our study revealed the presence of H. bovis with two haplotypes: HB3 and HB8. Another study based on molecular characterisation, conducted by Otranto et al [29], revealed similar results.…”
Section: Discussionmentioning
confidence: 99%